Manipulating charge and energy transfer between 2D atomic layers via heterostructure engineering - Liu, Xue (2021)
Two-dimensional (2D) van der Waals heterostructures have attracted enormous research interests due to their emergent electrical and optical properties. The comprehensive understanding and efficient control of interlayer couplings in such devices are crucial for realizing their functionalities, as well as for improving their performance. Here, we report a successful manipulation of interlayer charge transfer between 2D materials by varying different stacking layers consisting of graphene, hexagonal boron nitride, and tungsten disulfide. Under visible-light excitation, despite being separated by few-layer boron nitride, the graphene and tungsten disulfide exhibit clear modulation of their doping level, i.e., a change of the Fermi level in graphene as large as 120 meV and a net electron accumulation in WS2. By using a combination of micro-Raman and photoluminescence spectroscopy, we demonstrate that the modulation is originated from simultaneous manipulation of charge and/or energy transfer between each of the two adjacent layers.